EVALUATION OF THE EFFICACY OF BUPIVACAINE WITH CLONIDINE IN BILATERAL SUPERFICIAL CERVICAL PLEXUS BLOCK FOR THYROID SURGERY- A PROSPECTIVE OBSERVATIONAL STUDY - Dr. P. Rajkumar, Dr. M. Bhaskar, Dr. S. Manojkumar, Dr. K. Murugesan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Effective postoperative pain management is crucial for patients undergoingthyroid surgery to improve recovery and satisfaction. Systemic opioids, a traditional methodfor pain relief, are often associated with adverse effects like nausea, respiratory depression, andvomiting. A superficial cervical plexus block offers an alternative by providing targeted pain